Introducing changes at work: How voice behavior relates to management innovation. (26th June 2018) - Guzman, Felipe A.; Espejo, Alvaro
Summary: This multistudy research examines the unit‐level relationship between promotive voice behavior and management innovation. Study 1 utilizes multisource data from 62 work units and reports that willingness to discuss ideas mediates the unit‐level relationship between promotive voice and management innovation. The results of Study 1 also show that the unit's available resources make the relationship stronger between promotive voice and willingness to discuss ideas. Study 2 employs a scenario‐based design to constructively replicate and expand the results of Study 1, utilizing a sample of 100 working adults. The results of the second study also show that resource availability positively moderates the relationship between promotive voice and willingness to discuss ideas. Furthermore, Study 2 shows that the indirect effect of promotive voice on management innovation through willingness to discuss ideas is stronger when more resources are made available to the work units. This moderated‐mediation effect is shown to be significant using two different operationalizations of management innovation. The implications for theory and practice are discussed.